2022
DOI: 10.3390/cancers14153691
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements, Expression, and Clinical Significance of MYB and MYBL1 in Adenoid Cystic Carcinoma: A Multi-Institutional Study

Abstract: Adenoid cystic carcinoma (ACC) is an aggressive head and neck malignancy characterized by a t (6;9) translocation resulting in an MYB–NFIB gene fusion or, more rarely, an MYBL1 fusion. The true frequency and clinical significance of these alterations are still unclear. Here, we have used tissue microarrays and analyzed 391 ACCs and 647 non-ACC salivary neoplasms to study the prevalence, expression, and clinical significance of MYB/MYBL1 alterations by FISH and immunohistochemistry. Alterations of MYB or MYBL1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Our findings suggest that PARK2 is also a tumor suppressor in ACC that is associated with poor prognosis in a subset of tumors. This observation is further supported by our recent study showing that losses of sequences distal to the MYB locus in 6q23.3 preferentially occur in grade 3 tumors and are associated with poor OS in ACC [24]. Integrated transcriptomic and copy number profiling revealed several previously unrecognized events associated with ACC tumorigenesis.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our findings suggest that PARK2 is also a tumor suppressor in ACC that is associated with poor prognosis in a subset of tumors. This observation is further supported by our recent study showing that losses of sequences distal to the MYB locus in 6q23.3 preferentially occur in grade 3 tumors and are associated with poor OS in ACC [24]. Integrated transcriptomic and copy number profiling revealed several previously unrecognized events associated with ACC tumorigenesis.…”
Section: Discussionsupporting
confidence: 78%
“…FISH analysis of TMAs was done to study CNAs involving 1p36 represented by the marker genes CHD5 (1p36.31; CHD5/1q44 subtelomeric deletion probe from Cytocell, Cambridge, UK), KLHDC7A (1p36.13; KLHDC7A/CEN1 probe from Abnova, Taipei, Taiwan), Novel drivers and prognostic biomarkers in adenoid cystic carcinoma 257 and PARK2 (6q26) (PARK2 FISH probe from Empire Genomics (Buffalo, NY, USA) and a subtelomeric 6qter probe from Leica Biosystems, Nussloch, Germany), as previously described [24,27]. The protocols for pretreatment, hybridization, and posthybridization washes were as recommended by the manufacturers.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting the MYB oncogene in a clinical setting will require information about the MYB activation status. Since the mechanism of activation of MYB varies in T-ALL, analysis of the expression of MYB by RT-PCR, RNA-seq or immunohistochemistry are the preferable methods to determine whether the gene is activated or not ( 57 ). T-ALL patients with overexpression of MYB are thus candidates for MYB inhibitory treatments, whereas those with low or undetectable MYB levels are not.…”
Section: Discussionmentioning
confidence: 99%
“…Later work demonstrated that the rearrangement facilitates interaction of the MYB promoter with super‐enhancers to drive MYB overexpression 146 . A large, multi‐institutional study recently reported alterations in the MYB locus in 62.1% of ADCC tumors, with 39.1% of all tumors harboring MYB rearrangements, 16.1% with 3′ loss of the gene, and 3.1% with a gain of an intact MYB allele 147 . High MYB protein expression can also be found among rearrangement‐negative ADCCs, 142,145,148 suggesting that alternative mechanisms of MYB overexpression likely exist.…”
Section: Immunotherapy For Salivary Gland Cancersmentioning
confidence: 99%